Analisis Golden Section Pada Desain Tribun Utama Jakarta International Equestrian Park (JIEP) - Endar Sudarno; Nazaruddin Khuluk (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2024)
Jakarta International Equestrian Park (JIEP) is an international-scale equestrian sports facility featuring a grandstand design with well-balanced proportions. This study aims to analyze the application of the Golden Section (Golden Ratio) in the design of JIEP's main grandstand to determine the extent to which the Golden Section principles are implemented in its architectural design. The research employs a quantitative descriptive method, utilizing the Photo Match feature in SketchUp to reconstruct a three-dimensional model of the grandstand based on collected photographs. To enhance accuracy, direct measurements were also conducted using a laser distance meter. The analysis results indicate that while certain design elements of the grandstand align with the Golden Ratio, the application is not entirely consistent. This study provides new insights into the relevance of the Golden Section principle in the design of modern sports facilities.